Embedding photoacids into polymer opal structures: Synergistic effects on optical and stimuli-responsive features - Bitsch, Martin; Boehm, Anna Katharina; Grandjean, Alexander; Jung, Gregor; Gallei, Markus (Molecules, 2021)
Opal films with their vivid structural colors represent a field of tremendous interest and obtained materials offer the possibility for many applications, such as optical sensors or anti-counterfeiting materials. A convenient method for the generation of opal structures relies on the tailored design of core-interlayer-shell (CIS) particles. Within the present study, elastomeric opal films were combined with stimuli-responsive photoacids to further influence the optical properties of structurally colored materials. Starting from cross-linked polystyrene (PS) core particles featuring a hydroxy-rich and polar soft shell, opal films were prepared by application of the melt-shear organization technique. The photoacid tris(2,2,2-trifluoroethyl) 8-hydroxypyrene-1,3,6-trisulfonate (TFEHTS) could be conveniently incorporated during freeze-drying the particle dispersion and prior to the melt-shear organization. Furthermore, the polar opal matrix featuring hydroxylic moieties enabled excited-state proton transfer (ESPT), which is proved by spectroscopic evaluation. Finally, the influence of the photoacid on the optical properties of the 3-dimensional colloidal crystals were investigated within different experimental conditions. The angle dependence of the emission spectra unambiguously shows the selective suppression of the photoacid’s fluorescence in its deprotonated state.
Created from Fastlane, Scopus look-up
Keywords: Excited-state proton transfer; Fluorescence; Melt-shear organization; Opal film; Photoacid; Polymer particle synthesis